The Correlation of Knowledge Level on Stress Management with Mental Health of Hasanuddin University Students - Ridwan M. Thaha; Ani Asram; Muh Arsyad Rahman; Clement Lifoia (Media Kesehatan Masyarakat Indonesia, 2023)
University students lie in the age range of 19 to 25 years old. These students tend to face various psychological pressures which affect their mental health. One of the daily hassles that can cause stress to them is the thesis. Effective stress management may avoid students suffer from the pressures; thus, they can acclimatize to the stress itself. 54% out of 100 students at Hasanuddin University showed symptoms of stress to the initial data surveyed by the researcher. This research aims to find out whether there is a correlation between the knowledge level of stress management and the mental health of Hasanuddin University students in Makassar. This research is an analytic observational study with a cross-sectional approach. The population in this study were all students of Hasanuddin University class of 2018 (6,303 people in total) with a sample of 376 respondents. This research was held at Hasanuddin University. The data analysis technique used was the Chi-Square Test. The results showed that the knowledge level of stress management of students was mostly at the high level, which was 205 students (54.5%). The mental health state of the students was also in a good state with 203 students (54%) out of 376 students. The chi-square test showed that there was a significant association between the knowledge level of stress management and mental health of Hasanuddin University Makassar students with a p-value = 0.000 (<0.05). There is a relationship between the knowledge level of stress management with the mental health of students at Hasanuddin University.